BUBISHI: La Biblia del kárate - Pereda González, Pablo (Revista de Artes Marciales Asiáticas, 2012)
<span style="mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: IT; mso-bidi-font-weight: bold;" lang="IT">Patrick McCarthy. Madrid: Tutor, 2007. 224 páginas. 24x17 cm. I.S.B.N.: 978-84-7902-307-2.